Assessment of thoracic fluid volume in polytrauma patients with different body mass indexes under standard and restrictive infusion therapy regimens - М.О. Gogiya; S. V. Kursov; О.V. Markov; A.L. Lіashok (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Capillary-leak-driven fluid overload is a frequent complication in polytrauma, and obesity further amplifies this risk because standard body-weight– based resuscitation may overestimate the true distribution volume.